Identifying Barriers and Challenges in the Adoption of Building Information Modeling (BIM) Data for Project Portfolio Management (PPM) for Decision-Making - Regmi, Ram (My University, 2026)
Building Information Modelling (BIM) is a digital tool, which has gained popularity in the construction sector for enhancing design coordination, visualization and efficiencies at the project level. But it is still not widely used in Project Portfolio Management (PPM) or in decision-making for strategic planning. The barriers affecting the effective use of BIM information in PPM with emphasis on the decision-making process, specifically, in infrastructure related organizations are analysed in this thesis. The qualitative approach was used with semi-structured interviews with four industry practitioners, Project Director, BIM practitioner, Infrastructure and construction Project Managers from Finland and Nepal. Thematic analysis method was used to analyse the data based on the categories of technical, organizational and managerial barriers that have been identified in the previous research. The findings show that there are interrelated barriers in three dimensions that cause BIM to be underutilized when making portfolio decisions. Interoperability problems, the absence of common data formats, and the integration of several software systems present technical challenges. Organizational barriers include the lack of formal BIM data handover processes, silo mentality among the teams, and unwillingness to change among the highly experienced professionals. Managerial barriers are poor awareness of the strategic benefits of BIM among managers, uncertainty about the potential ROI and lack of skills to utilize BIM for strategic analysis instead of operational work. The results indicate that BIM is not used primarily as a strategic decision support system but rather as a design and a coordination tool. This leads to poor quality of portfolio decisions, limited learning across projects and poor strategic fit. The results reveal that BIM underutilization is not just a technical problem but a systemic problem that is related to the organizational structure and managerial practices. A contribution is made by this study through the provision of a structured barrier framework and the relationships between BIM adoption barriers and the loss of strategic value and the quality of decision-making. It also offers actionable guidance to industry stakeholders, BIM specialists, portfolio managers and leaders to enhance the BIM-PPM relationship and foster data-driven PPM.
Keywords: project management; decision making; information management; portfolios; digital support; construction projects; Strategic Project Management; Master’s Programme in Industrial Engineering and Management